2018
DOI: 10.1111/dom.13202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a glucagon receptor antibody (REMD‐477) in type 1 diabetes: A randomized controlled trial

Abstract: The aim of the current study (Clinical trial reg. no. NCT02715193, clinicaltrials.gov) was to study the efficacy and safety of REMD-477, a glucagon receptor antagonist, in type 1 diabetes. This was a randomized controlled trial in which 21 patients with type 1 diabetes were enrolled. Glycaemic control and insulin use were evaluated in outpatient and inpatient settings, before and after a single 70-mg dose of REMD-477 (half-life 7-10 days) or placebo. Inpatient insulin use was 26% (95% CI, 47%, 4%) lower 1 day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Previous studies suggest that some of the compensatory mechanisms in response to Gcgr deletion act by increasing insulin action. Hence, Gcgr −/− mice exhibit increased insulin sensitivity [36] , and treatment with a monoclonal antibody against Gcgr reduces insulin requirements in T1DM humans [37] . Our data suggest that factors other than different levels of basal plasma c-peptide (insulin) or insulin signaling measured as pAKT levels must contribute to the increased insulin action due to loss of GCGR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that some of the compensatory mechanisms in response to Gcgr deletion act by increasing insulin action. Hence, Gcgr −/− mice exhibit increased insulin sensitivity [36] , and treatment with a monoclonal antibody against Gcgr reduces insulin requirements in T1DM humans [37] . Our data suggest that factors other than different levels of basal plasma c-peptide (insulin) or insulin signaling measured as pAKT levels must contribute to the increased insulin action due to loss of GCGR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from our group and others have shown that REMD 2.59, a fully competitive antagonistic human GCGR monoclonal antibody (mAb), has a strong hypoglycemic effect in type 1 diabetic (T1D) and T2D rodents and non-human primates 6–10. Importantly, a phase I/II randomized clinical trial showed that REMD 477, another human GCGR mAb that differs by only one amino acid (which is not involved in glucagon binding) and has an affinity for the GCGR equivalent to that of REMD 2.59, improved glycemic control in patients with T1D, and no serious adverse effects were detected 11. Interestingly, our previous study discovered that REMD 2.59 induced pancreatic β-cell regeneration, which derived at least partially from transdifferentiation of pancreatic α-cells or δ-cells 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent proof-of-concept trial, one of these agents showed potential for improved glycemic control and decreased insulin doses in type 1 diabetes. 72 However, potential side effects of other developmental agents in this class include weight gain, increased cholesterol, and alpha-cell hyperplasia. Further research is needed to determine the clinical utility of this class.…”
Section: Incretin Mimeticsmentioning
confidence: 99%